Dissolution Enhancement of Atorvastatin Calcium by Cocrystallization - Reham Al-Kazemi; Yacoub Al-Basarah; Aly Nada (Tabriz University of Medical Sciences, 2019)
Purpose: To enhance the dissolution rate of the poorly soluble drug atorvastatin calcium (ATC) by cocrystallization with selected coformers. Enhancement of the dissolution rate and solubility of the drug, which is classified as Class II of the Biopharmaceutical Classification System (BCS), is expected to enhance the bioavailability. Methods: Two methods were used for preparing the cocrystals, solvent drop grinding (SDG) and solvent evaporation (SE) method using 1:1, 1:3, and 1:10 drug-coformer molar ratios. Glucosamine hydrochloride (GluN) and nicotinamide (NIC) were investigated as coformers. The cocrystals, their physical mixtures, and the raw ATC were characterized by fourier transform infrared (FTIR spectroscopy), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), mass spectroscopy (MS), scanning electron microscopy (SEM), solubility, and dissolution rate studies. Results: SDG and SE were effective in improving the dissolution rate of ATC with both coformers. Drug: coformer ratio 1:3 was optimum. The solubility values for ATC, GluN-, and NIC-cocrystals were 26, to 35 and 50 µg/mL, respectively. The dissolution rate of ATC from cocrystals was > 90% after 5 minutes, compared to 41% untreated ATC. Conclusion: Cocrystallization significantly improved the solubility and dissolution, in comparison to the untreated ATC.